2013
DOI: 10.1136/archdischild-2012-303572
|View full text |Cite
|
Sign up to set email alerts
|

Online support for parents of preterm infants: a qualitative and content analysis of Facebook ‘preemie’ groups

Abstract: Facebook groups related to preterm birth have become a popular tool for fundraising and awareness-raising. However, most group members use these forums for information sharing and interpersonal support. Given their popularity and reach, further research is warranted to understand the motivations, implications and risks of dynamic online communication among parents of preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 15 publications
1
44
0
4
Order By: Relevance
“…This is because social media helps to achieve a better perspective about health problems and eliminate sources of concern. Posting, sharing, and commenting on health-related issues, joining or developing online health communities, and exchanging information about health issues (Thoren et al, 2013) are social reinforcements that enable increased access to information and social advancement (DiMaggio & Bonikowski, 2008) and prompt a ''health empowerment'' process (Dutta-Bergman, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because social media helps to achieve a better perspective about health problems and eliminate sources of concern. Posting, sharing, and commenting on health-related issues, joining or developing online health communities, and exchanging information about health issues (Thoren et al, 2013) are social reinforcements that enable increased access to information and social advancement (DiMaggio & Bonikowski, 2008) and prompt a ''health empowerment'' process (Dutta-Bergman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Social media have revolutionized communication, resulting in the creation of online social relationships on platforms such as Facebook and Twitter (Thoren, Metze, Bührer, & Garten, 2013), expanding social ties and increasing psychological well-being (Chen & Lee, 2013;Nabi, Prestin, & So, 2013). Diverse sources of relevant information located in social media, ICQ, chats, health forums, etc.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the awareness groups had the most members, while the support groups generated the greatest number of posts. Thoren et al [12] examined the content of Facebook groups focusing on premature infants. Similar to findings from breast cancer groups, they found that most premature infant groups were devoted to fundraising or awareness purposes and that these groups had the most members.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the information age has engendered public awareness of the development of medical science and technology; consequently, parents of critically impaired infants are often encouraged by the use of the Internet and social networking support groups to request lifesustaining treatment to save their child from death (Thoren et al 2013). Parent-doctor disagreements concerning withdrawal or withholding of lifesustaining treatment for severely ill infants are generally resolved in the hospital setting.…”
Section: Introductionmentioning
confidence: 98%